Sofosbuvir, ribavirin and pegylated interferon for a daclatasvir-resistent genotype 3 hepatitis C virus: case report and review - Mucenic, Marcos (2019)
Chronic Hepatitis C relapse after liver transplantation can lead to graft failure within a short time period. The high efficacy and good safety profile of direct-acting antivirals has led to consensual recommendations for using interferon-free treatment after liver transplantation. However, pegylated interferon may still be required for genotype 3 non-responders. We treated a liver graft recipient with grade 1 fibrosis in the biopsy with daclatasvir and sofosbuvir for 12 weeks. He did not respond and progressed to grade 3 fibrosis. Lacking other options, we obtained a sustained virological response with pegylated interferon, ribavirin and sofosbuvir for 12 weeks. The combination of pegylated interferon, ribavirin and sofosbuvir is a viable option after the failure of direct acting antivirals in economically disadvantaged countries.